Dialogue and religious plurality – challenges of contemporary society - Brînzea, Nicolae; Croitoru, Mihai Marian (Technium Social Sciences Journal, 2022)
Starting from the premise that man is a dichotomous being, with a material body and a spiritual, immortal soul, today's society is looking for answers to perhaps the most important question that refers to salvation, namely: how can we know today's religions, Christian and non-Christian, the authentic meaning of the human soul and implicitly its path in eternity? For such answers, in the context of religious pluralism, interreligious dialogue is imperative, through which Christian and non-Christian religions offer their answers, so that the result can be experienced by society.